Activation of innate immunity accelerates sialoadenitis in a mouse model for Sjögren’s Syndrome-like disease - Nandula, Seshagiri-Rao (2011)
OBJECTIVE: Sjögren’s syndrome is a chronic autoimmune disorder characterized by progressive lymphocytic infiltration within the salivary and lacrimal glands. The current study was undertaken to investigate the effects of innate immunity activation on sialoadenitis in a mouse strain genetically susceptible for development of Sjögren’s syndrome-like disease. METHODS: Female New Zealand Black × New Zealand White F1 mice were repeatedly treated with toll-like 3 receptor agonist poly(I:C). Submandibular glands were investigated at different time points for sialoadenitis by immunohistochemistry and for gene expression of different chemokines by quantitative PCR. Submandibular gland infiltrating cells were characterized by flow cytometry. RESULTS: Poly(I:C) treatment significantly upregulated the expression of multiple chemokines within the submandibular glands. The severity and incidence of sialoadenitis was considerably higher in poly(I:C) treated mice. There was a preponderance of dendritic cells and NK cells in the initial inflammatory cell infiltrates and these were followed by CD4+ T cells. CONCLUSIONS: Our data clearly demonstrates that systemic activation of innate immunity accelerates sialoadenitis in a mouse model for Sjögren’s syndrome-like disease. These findings suggest that chronic activation of innate immunity can influence certain features of Sjögren’s syndrome.